2016
DOI: 10.1371/journal.pone.0164936
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Direct Renin Inhibitor and Angiotensin Receptor Blocker on Albuminuria in Hypertensive Patients with Type 2 Diabetes. A Randomized Controlled Trial

Abstract: BackgroundIn patients with diabetes, albuminuria is a risk marker of end-stage renal disease and cardiovascular events. An increased renin-angiotensin system activity has been reported to play an important role in the pathological processes in these conditions. We compared the effect of aliskiren, a direct renin inhibitor (DRI), with that of angiotensin receptor blockers (ARBs) on albuminuria and urinary excretion of angiotensinogen, a marker of intrarenal renin-angiotensin system activity.MethodsWe randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Studies have shown that the use of ACE-i/ARB suppresses both plasma and intrarenal RAS activation ( 24 , 25 ). However, approximately 5%–20% of patients treated with ACE inhibitors cannot tolerate these drugs because of dry cough, angioedema, hypotension, hyperkalemia, or renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the use of ACE-i/ARB suppresses both plasma and intrarenal RAS activation ( 24 , 25 ). However, approximately 5%–20% of patients treated with ACE inhibitors cannot tolerate these drugs because of dry cough, angioedema, hypotension, hyperkalemia, or renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the characteristics of the included studies and participants. Of all the included studies, two compared the monotherapy of direct renin inhibitors with angiotensin receptor blocker (ARB) [11,13], while two studies compared the combination of direct renin inhibitors with monotherapy of ARB or angiotensin-converting enzyme inhibitor (ACEI) [9,12]. The dose for ARB, ACEI and direct renin inhibitors varied in the included study.…”
Section: Resultsmentioning
confidence: 99%
“…It is well recognized that one of the most effective therapeutic approaches for lowering the risk of cardiovascular and renal events in diabetic patients is to treat microalbuminuria by blocking the renin-angiotensin-aldosterone pathway [ 13 ]. In the present meta-analysis, direct renin inhibitor was associated with a significant reduction in UACR and also improvement in other outcomes including remission from microalbuminuria to normal albuminuria and progression from microalbuminuria to macroalbuminuria.…”
Section: Reviewmentioning
confidence: 99%
“…In contrast, there are also a number of studies (n = 21) which investigated the effect of using monotherapies, and report some benefits and effects on renal outcomes and/or RAAS blockade efficacy among DN patients [16][17][18][19]21,24,[26][27][28][29][30][31]33,38,40,46,47,53,[57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies do not report significant benefits of these therapies when used in combination. ARBs have also shown to be a more superior and potent treatment option compared to others among DN patients [16,30]. In six studies, the therapies appeared to have a similar effect or were unable to show any effect or benefit on varied renal outcomes [1,20,23,25,36,44].…”
Section: Discussionmentioning
confidence: 99%